SUSTAINABILITY IN THEORY AND PRACTICE - Jakab, Nora (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
In recent years, there has been a growing focus on sustainability and a fair transition. The study is timely given the need for EU Member States to prepare territorially equitable transition plans in order to access the €17.5 billion Equitable Transition Fund. In my study, I seek to answer the question of how to make the economy sustainable and competitive, which cannot be imagined without the sustainability of social processes. Would a fair transition be the social side of economic sustainability? The question that has arisen is: what does a fair transition mean? What kind of programme does it involve, so that no one is left out?